2019
DOI: 10.5863/1551-6776-24.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Uncomplicated Urinary Tract Infection in Ambulatory Primary Care Pediatrics: Are We Using Antibiotics Appropriately?

Abstract: OBJECTIVES Antimicrobial stewardship programs target antimicrobial use within the inpatient care setting. However, most antimicrobials are prescribed at ambulatory sites. We aim to determine the appropriateness of the diagnosis and treatment of uncomplicated urinary tract infection (UTI) in children within the outpatient setting at our institution, and to evaluate the cost of antibiotic treatment in our patient cohort. METHODS This retrospective study was conducted by reviewing electronic record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…10 Prescribing practices for UTIs are variable and problems exist, including the use of overly broad antibiotics and treatment in the absence of true infection. 11,12 To investigate antibiotic prescribing practices for suspected UTIs, we primarily sought to determine whether empiric antibiotic selection was appropriate for suspected UTIs in children and adults. Secondarily, we set out to analyze frequency of antibiotic prescription in the absence of true infection and whether variation in appropriate antibiotic selection existed between specific provider groups, including attending physicians, resident physicians, physician assistants, and nurse practitioners.…”
Section: How Does This Improve Population Health?mentioning
confidence: 99%
“…10 Prescribing practices for UTIs are variable and problems exist, including the use of overly broad antibiotics and treatment in the absence of true infection. 11,12 To investigate antibiotic prescribing practices for suspected UTIs, we primarily sought to determine whether empiric antibiotic selection was appropriate for suspected UTIs in children and adults. Secondarily, we set out to analyze frequency of antibiotic prescription in the absence of true infection and whether variation in appropriate antibiotic selection existed between specific provider groups, including attending physicians, resident physicians, physician assistants, and nurse practitioners.…”
Section: How Does This Improve Population Health?mentioning
confidence: 99%
“…Diagnoses frequently encountered in the outpatient setting categorized as "low-hanging fruit" ripe for outpatient AS interventions include acute otitis media (AOM), pharyngitis, acute bacterial sinusitis, skin and soft-tissue infections, community-acquired pneumonia, and urinary tract infections. [77][78][79][80][81] Macrolides and third-generation oral cephalosporins like cefdinir are often prescribed inappropriately as first-line agents for treatment of pharyngitis and communityacquired pneumonia. 78,80,82 In one study conducted within a single large US healthcare system, pediatricians were more likely than advanced practice providers and non-pediatricians to have: 1) prescribed antibiotics for pediatric sinusitis that were concordant with national guidelines and 2) appropriately withheld antibiotics when upper respiratory infections were diagnosed.…”
Section: National/international Stewardshipmentioning
confidence: 99%
“…The analysis of available data showed that the incidence of oligoanuria was 46.1% in the T-group and 52.5% in the H-group. The rates of pyuria, which was defined as a urine WBC count of >5/high-power field or dipstick positivity for leukocyte esterase ( 25 ), and the absence of pathologic casts were 73.0%/78.9% in the T-group and 57.6%/68.4% in the H-group, respectively. The incidence of bilateral kidney enlargement on imaging was 61.5% in the T-group and 68.4% in the H-group.…”
Section: Discussionmentioning
confidence: 99%